Dramatically accelerated selective oxygen-atom transfer by a nonheme iron(IV)-oxo complex: Tuning of the first and second coordination spheres - Widger, Leland R.; Davies, Casey G.; Yang, Tzuhsiung; Siegler, Maxime A.; Tröppner, Oliver; Jameson, Guy N.L.; Ivanovic-Burmazovic, Ivana; Goldberg, David P. (Journal of the American Chemical Society, 2014)
The new ligand N3PySR and its Fe complex [Fe(N3PySR)](BF) (1) are described. Reaction of 1 with PhIO at -40 C gives metastable [Fe (O)(N3PySR)] (2), containing a sulfide ligand and a single amide H-bond donor in proximity to the terminal oxo group. Direct evidence for H-bonding is seen in a structural analogue, [Fe (Cl)(N3PySR)](BF) (3). Complex 2 exhibits rapid O-atom transfer (OAT) toward external sulfide substrates, but no intramolecular OAT. However, direct S-oxygenation does occur in the reaction of 1 with mCPBA, yielding sulfoxide-ligated [Fe (N3PyS(O)R)](BF) (4). Catalytic OAT with 1 was also observed. © 2014 American Chemical Society.